2022
DOI: 10.3389/fbioe.2022.995879
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Three-dimensional printed prosthesis reconstruction for patello-femoral large osteochondral defects in a patient with distal femoral giant cell tumour: A case report

Abstract: Background: The restoration and reconstruction of patello-femoral large osteochondral defects caused by bone tumours are challenging because of the local recurrence rate and the joint’s mechanical complexity. Although three-dimensional (3D)-printed prostheses are commonly adopted for tumour-induced bone defect reconstruction, patello-femoral osteochondral reconstruction with 3D-printed prostheses is rarely reported.Case presentation: A 44-year-old female patient with progressive swelling and pain in the left k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Osseointegration is essential for the long-term stability of the prosthesis ( Yuan et al, 2022 ); otherwise, aseptic loosening is inevitable. Follow-up results showed that good osseointegration could be achieved at the bone–implant interface, indicating that this 3D-printed porous implant is highly histocompatible and fully meets the complex mechanical environment of the lumbosacral region.…”
Section: Discussionmentioning
confidence: 99%
“…Osseointegration is essential for the long-term stability of the prosthesis ( Yuan et al, 2022 ); otherwise, aseptic loosening is inevitable. Follow-up results showed that good osseointegration could be achieved at the bone–implant interface, indicating that this 3D-printed porous implant is highly histocompatible and fully meets the complex mechanical environment of the lumbosacral region.…”
Section: Discussionmentioning
confidence: 99%